2013
DOI: 10.1242/jcs.118844
|View full text |Cite
|
Sign up to set email alerts
|

Principles of the mitochondrial fusion and fission cycle in neurons

Abstract: SummaryMitochondrial fusion-fission dynamics play a crucial role in many important cell processes. These dynamics control mitochondrial morphology, which in turn influences several important mitochondrial properties including mitochondrial bioenergetics and quality control, and they appear to be affected in several neurodegenerative diseases. However, an integrated and quantitative understanding of how fusion-fission dynamics control mitochondrial morphology has not yet been described. Here, we took advantage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
138
2
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(149 citation statements)
references
References 24 publications
5
138
2
4
Order By: Relevance
“…We also show that TBA shifts the mitochondrial fission-fusion balance of striatal neurons towards more fusion, possibly because increasing microtubule-dependent movement increases fusion probability [45,46], particularly when mitochondrial contact probability is otherwise reduced by low motility. Inhibition of mitochondrial fission is emerging as a pharmacological strategy to counteract excessive mitochondrial fission in neurodegenerative diseases, such as HD [47,48].…”
Section: Accepted Manuscriptmentioning
confidence: 70%
“…We also show that TBA shifts the mitochondrial fission-fusion balance of striatal neurons towards more fusion, possibly because increasing microtubule-dependent movement increases fusion probability [45,46], particularly when mitochondrial contact probability is otherwise reduced by low motility. Inhibition of mitochondrial fission is emerging as a pharmacological strategy to counteract excessive mitochondrial fission in neurodegenerative diseases, such as HD [47,48].…”
Section: Accepted Manuscriptmentioning
confidence: 70%
“…As all mitochondrial fusion and fission proteins are present in the cells, we cannot determine which proteins actually are responsible for the observed morphology. However, overexpression of MFN2 in neurons or in pulmonary artery smooth muscle cells induced mitochondrial elongation (8,36); hence, increased fusion and especially increased levels of MFN2 may functionally influence mitochondrial hyperfusion. Thus up- , and 25% CSE; n ϭ 3-6 ϩ SE.…”
Section: Discussionmentioning
confidence: 99%
“…Incomplete fission can result in a tangle of interconnected mitochondria and incomplete fusion can result in mitochondrial aggregates, thus motility's effect on the processes seems clear (Chen and Chan, 2009). On the other hand, it has been shown that loss of Miro, which inhibits motility, subsequently inhibits fusion (Cagalinec et al, 2013). It is logical to assume that motility facilitates fission and fusion as at least one mitochondrion must move toward another for fusion to take place and once divided the organelles must move apart to remain separate.…”
Section: Discussion the Role Of Microtubules In Mitochondrial Dynamicsmentioning
confidence: 99%
“…Additionally, we examined whether or not cluA − mitochondrial morphology is dependent upon these cytoskeletal components and how these components affect motility of the cluA − mitochondria. Finally, due to mounting evidence linking impaired fission and/or fusion to aberrant mitochondrial motility and cellular health (Cagalinec et al, 2013), we assessed the influence of the cytoskeleton on mitochondrial fission and fusion.…”
Section: Introductionmentioning
confidence: 99%